PENTINGNYA SEX EDUCATION UNTUK ANAK USIA DINI SEBAGAI PENCEGAHAN PELECEHAN SEKSUAL - Srie Maya Pratiwi; Gilar Gandana; Qonita (LPPM Universitas Cipta Mandiri, 2024)
The increasing incidence of sexual abuse among children is a serious issue requiring urgentattention. Sexual abuse not only impacts children physically but also mentally and emotionally,potentially damaging their thought patterns and psychological well-being. This research aims to highlight the importance of sex education from an early age as a preventive measure against sexualabuse. Data indicates that the rate of sexual abuse crimes in Indonesia remains high, with manycases involving children under the age of 10. Early sex education is considered crucial to equipchildren with accurate knowledge about sexuality and healthy boundaries. A literature review wasconducted to explore the concept of sex education, its objectives, and implementation methods. Theresults indicate that sex education aims to provide understanding of the body, healthyinterpersonal relationships, and moral values. This research emphasizes the importance of early sexeducation as an effective preventive measure to protect children from sexual abuse. By providingaccurate understanding of sexuality from a young age, children can develop healthy attitudestowards their bodies and interpersonal relationships, and can identify and protect themselves fromrisky situations. Moreover, the involvement of parents and educators in providing appropriate andcomprehensive sex education is crucial to creating a safe and supportive environment for children.Thus, sex education from an early age is not only the responsibility of individuals but also aninvestment in a better future for the next generation.